Budaya Organisasi Dan Komitmen Pegawai: Kunci Meningkatkan Kinerja Di Sektor Publik - Carolina Apriliyantia; Deden Sutisna (Yayasan Riset dan Pengembangan Intelektual, 2024)
This study aims to analyze the influence of organizational culture and organizational commitment on employee performance at the Regional Revenue Agency (BAPENDA) of Serang City. The background of this study is based on the phenomenon of low employee performance that does not fully reflect organizational effectiveness, even though work targets have been achieved administratively. The method used was a quantitative method with a causal associative approach. Data collection was conducted by distributing questionnaires to 164 employees. Data analysis used multiple linear regression to test the partial and simultaneous effects between the independent and dependent variables. The results showed that, partially, organizational culture had no significant effect on employee performance. Conversely, organizational commitment had a significant and positive effect on performance. Simultaneously, organizational culture and organizational commitment significantly influenced employee performance. These findings indicate that performance improvement is more effective through strengthening organizational commitment, without ignoring the role of organizational culture as a supporting factor. The implications of this study recommend the importance of managerial strategies that focus on strengthening employee loyalty, belonging, and responsibility, as well as work culture reform to encourage sustainable organizational effectiveness